The challenge of following a research line within the framework of student scientific production - Guillen León, Laura Adalys; Vitón Castillo, Adrián Alejandro (Revista de Ciencias Médicas de Pinar del Río, 2022)
The challenge of following a research line within the framework of student scientific production